Exergy analysis of district energy systems and comparison of their exergetic, energetic and environmental performance. (29th June 2020) - Ahmadian, Ehsan; Schmidt, Ralf-Roman
This paper investigates the advantages of performing exergy analysis for thermodynamic systems consisting of a district heating network (DHN) by comparing the exergy performance with energetic and environmental performance of three case studies in Austria. Furthermore, the effect of influential parameters such as energy source type, conversion technology, supply/return temperature and reference temperature on exergy performance of the system was investigated. An initial literature review and analysis of the case studies showed that the most influential factor on exergy performance of a system was the type of energy source and its conversion technology. Although lowering the supply temperature of DHN can increase the exergy efficiency of the system, changing reference temperature did not show a clear relationship with exergy efficiency. Finally, no clear relationship between energy and exergy efficiencies of the system was discovered; nevertheless, the higher the exergy efficiency of a system the lower the direct CO2 emissions from it.